Synthesis and pharmacology of new psychoactive substance 5F‐CUMYL‐P7AICA, a scaffold‐ hopping analog of synthetic cannabinoid receptor agonists 5F‐CUMYL‐PICA and 5F‐CUMYL‐PINACA. Issue 2 (1st October 2018) - Banister, Samuel D.; Adams, Axel; Kevin, Richard C.; Macdonald, Christa; Glass, Michelle; Boyd, Rochelle; Connor, Mark; McGregor, Iain S.; Havel, Christopher M.; Bright, Stephen J.; Vilamala, Mireia Ventura; Lladanosa, Cristina Gil; et al.
Abstract: Synthetic cannabinoid receptor agonists (SCRAs) are a dynamic class of new psychoactive substances (NPS), with novel chemotypes emerging each year. Following the putative detection of 5F‐CUMYL‐P7AICA in Australia in 2016, the scaffold‐hopping SCRAs 5F‐CUMYL‐PICA, 5F‐CUMYL‐PINACA, and 5F‐CUMYL‐P7AICA were synthesized and characterized by nuclear magnetic resonance (NMR) spectroscopy, gas chromatography–mass spectrometry (GC–MS), and liquid chromatography–quadrupole time‐of‐flight–MS (LC–QTOF–MS). Since little is known of the pharmacology of 7‐azaindole SCRAs like 5F‐CUMYL‐P7AICA, the binding affinities and functional activities of all compounds at cannabinoid type 1 and type 2 receptors (CB1 and CB2, respectively) were assessed using tritiated radioligand competition experiments and fluorescence‐based plate reader membrane potential assays. Despite CB1 binding affinities differing by over two orders of magnitude ( K i = 2.95–174 nM), all compounds were potent and efficacious CB1 agonists (EC50 = 0.43–4.7 nM), with consistent rank order for binding and functional activity (5F‐CUMYL‐PINACA >5F‐CUMYL‐PICA >5F‐CUMYL‐P7AICA). Additionally, 5F‐CUMYL‐P7AICA was found to exert potent cannabimimetic effects in mice, inducing hypothermia (6°C, 3 mg/kg) through a CB1 ‐dependent mechanism. Abstract : The putative synthetic cannabinoid receptor agonist (SCRA) 5F‐CUMYL‐P7AICA was synthesized, along with its scaffold‐hopping analogs 5F‐CUMYL‐PICA and 5F‐CUMYL‐PINACA, following detection in a new psychoactive substance (NPS) product in Australia. 5F‐CUMYL‐P7AICA was differentiated from 5F‐CUMYL‐PICA and 5F‐CUMYL‐PINACA by nuclear magnetic resonance (NMR) spectroscopy, gas chromatography–mass spectrometry (GC–MS), and liquid chromatography–quadrupole time‐of‐flight–MS (LC–QTOF–MS). Like 5F‐CUMYL‐PICA and 5F‐CUMYL‐PINACA, 5F‐CUMYL‐P7AICA demonstrated potent cannabinoid activity in vitro and in vivo.